2018
DOI: 10.7554/elife.34226
|View full text |Cite
|
Sign up to set email alerts
|

Gene family innovation, conservation and loss on the animal stem lineage

Abstract: Choanoflagellates, the closest living relatives of animals, can provide unique insights into the changes in gene content that preceded the origin of animals. However, only two choanoflagellate genomes are currently available, providing poor coverage of their diversity. We sequenced transcriptomes of 19 additional choanoflagellate species to produce a comprehensive reconstruction of the gains and losses that shaped the ancestral animal gene repertoire. We identified ~1944 gene families that originated on the an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
320
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4
2

Relationship

1
9

Authors

Journals

citations
Cited by 187 publications
(332 citation statements)
references
References 181 publications
(268 reference statements)
11
320
1
Order By: Relevance
“…6) to a transition from a holopelagic to a biphasic pelago-benthic life cycle in the stem-benthozoan lineage. This particular result furthers a growing picture of metabolic and chaperone gene loss and gene innovation in early animal evolution (ERIVES AND FASSLER 2015;RICHTER et al 2018).…”
Section: Discussionsupporting
confidence: 52%
“…6) to a transition from a holopelagic to a biphasic pelago-benthic life cycle in the stem-benthozoan lineage. This particular result furthers a growing picture of metabolic and chaperone gene loss and gene innovation in early animal evolution (ERIVES AND FASSLER 2015;RICHTER et al 2018).…”
Section: Discussionsupporting
confidence: 52%
“…Some of the genes of this pathway originated in Choanozoans but the core pathway is clearly already established in sponges, tens of million years before the Cambrian explosion. In animals the Wnt pathway has a conserved role in: anterior-posterior axis formation in embryos, in organogenesis, and in tissue homeostasis (1)(2)(3). Dysregulation of the Wnt pathway plays a role in various human diseases including skeletal, cardiac vascular diseases (4), and cancer (5).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, S. rosetta is just one tip on the 285 choanoflagellate branch. A recent survey of 21 choanoflagellate transcriptomes revealed that choanoflagellates are at least as genetically diverse as animals (Richter et al, 2018), with other species retaining genetic pathways or exhibiting behaviors that are not found in S. rosetta (e.g., Marron et al, 2013;Leadbeater, 2015;Brunet et al, 2019). Together with future findings from S. rosetta, we anticipate that the establishment of genome editing in other choanoflagellates will 290 provide an increasingly complete portrait of the last common ancestor of choanoflagellates and animals.…”
Section: Discussionmentioning
confidence: 78%